Quelques exemples d’analyse des corpus en vue de la traduction - Vetulani, Grażyna (Studia Romanica Posnaniensia, 2007)
Intensive works by (first) computer scientists and (then) linguists in order to obtain Automatic Translation Systems started already in the late 40-ties. Since that time many things have changed in the field of tools and methodologies like for example creation of basic electronic resources as corpora and dictionaries or the lexicon-grammar framework. This paper presents some language engineering tools recently developed (with participation of the Author) for Polish and claims their interest for the Translation Community.